Analyzing private dental clinics in Riyadh City, Saudi Arabia - Fahd Alsalleeh; Mashari Alohali; Marshed Alzeer; Meshal Aloseimi; Nassr Almuflehi; Sattam Alshiha (Elsevier, 2018)
Aim: To survey private dental clinics and analyze its clinicians in Riyadh city Saudi Arabia. Materials and methods: Private dental clinics that had been registered with the Ministry of Health (MOH), Health Affairs System and accepted to participate were included. All clinics were visited to collect data. Number of practicing dentists, nationality, and their specialty classification were recorded. The location and year of establishment of each dental center were also collected. Results: Out of 236 private dental clinics registered in MOH, 162 clinics accepted to participate. The total number of dentists in these clinics was 877. The majority of dentists were males (63.97%). The percentage of non-Saudi dentists were 86.66%, and Syrians dentists being the highest group (40.25%). The primary specialty of dentists was general dentistry (70.5%). The location of private dental clinics was found to be concentrated in some areas and not evenly distributed in Riyadh city. There were 49 clinics in Olaya, followed by 45 clinics in Rawdha municipality. Conclusion: Private dental clinics in Riyadh city are operated mainly by Non-Saudi dentists. Moreover, there is still a need for more female dentists and dental specialists. There are areas in Riyadh city that lack private dental clinics. Keywords: Dentists, Private dental centers, Workforce